Indonesian Local Wisdom as the Content for an English Business Presentation: Students’ Understanding and Perception. - Melania Wiannastiti; Januarius Mujiyanto; Dwi Anggani Linggar Bharati (Universitas Negeri Semarang, 2021)
This era of technology compels university students to equip themselves with virtual business presentation skills. Generally, a business presentation in English is related to business content which is used specifically for marketing or selling. However, for a certain purpose, a business presentation has a specific purpose to give essential information to the audience. This research study is a part of dissertation research that aims to reveal the students' understanding of local wisdom namely Pancasila – Indonesian national values as the content of an English business presentation and reveal their perception toward the use of the content. A questionnaire was distributed to sixty students in two classes joining the English for Business Presentation Course at BINUS University, Jakarta. A virtual interview for ten students from both classes was also conducted to support the data found. A mixed-method analysis was used to analyze the data found. The result shows that their understanding of Pancasila; the local wisdom as the content is not high as it is expected, however, they perceive quite high for the use of Pancasila as the content for a business presentation.